New perspectives in the diagnosis of thyroid follicular lesions. (May 2017) - Baldini, Enke; Sorrenti, Salvatore; Tartaglia, Francesco; Catania, Antonio; Palmieri, Andrea; Pironi, Daniele; Filippini, Angelo; Ulisse, Salvatore
Abstract: Thyroid nodules are very common, affecting 19%–67% of the adult population. However, about 10% of them harbor a malignant lesion. Consequently, the first aim in their clinical evaluation is to exclude malignancy. Fine-needle aspiration cytology (FNAC) represents the main diagnostic tool for the evaluation of thyroid nodules. However, FNAC has a main diagnostic limit, namely cellular atypias of indeterminate significance, which require surgical excision and histological examination to differentiate benign from malignant lesions. Histology reports show that approximately 80% of these patients harbor a benign lesion. Therefore, in order to reduce unnecessary thyroidectomy, over the last years, the cytological classification of thyroid nodules has been revised and a number of new instrumental and molecular approaches have been proposed. In the present article, we will attempt to summarize the most recent cytological, molecular and echographic strategies to enhance the diagnostic accuracy of preoperative thyroid follicular lesions. In particular, we will discuss the new cytological classifications from the Bethesda System for Reporting Thyroid Cytopathology (BSRTC), the British Thyroid Association-Royal College of Pathologists (PTA-RCPath) and the new Italian Society for Anatomic Pathology and Cytology (SIAPEC 2014. We will review molecular tests evaluated to ameliorate follicular lesion diagnosis as well as the clinical utility of the new echographic Thyroid Imaging Reporting and Data System (TI-RADS) score. Highlights: The FNAC shows low accuracy in the thyroid follicular lesion (FL) diagnosis. Molecular diagnosis may improve FNAC diagnostic accuracy of FL. TIRADS may offer a better risk stratification of follicular lesion malignancy.